On Kadison-Schwarz Type Quantum Quadratic Operators on - Farrukh Mukhamedov; Abduaziz Abduganiev (Abstract and Applied Analysis)
We study the description of Kadison-Schwarz type quantum quadratic operators (q.q.o.) acting from into . Note that such kind of operators is a generalization of quantum convolution. By means of such a description we provide an example of q.q.o. which is not a Kadison-Schwartz operator. Moreover, we study dynamics of an associated nonlinear (i.e., quadratic) operators acting on the state space of .